PERANCANGAN E-BAROKAH UMANA’ DI MADRASAH TA’HILIYAH IBRAHIMY - Moch Maulana Ridho Kurniawan; Farihin Lazim (CV. ALIM'SPUBLISHING, 2025)
Madrasah Ta'hiliyah Ibrahimy, part of the Salafiyah Syafi'iyah Islamic Boarding School, is a semi-formal educational institution founded in 1986 by KH. Saifuddin Maksum. This institution focuses on student education and is under the coordination of the Ibrahimy Islamic Institute (IAII). One of the main problems faced by Madrasah Ta'hiliyah is the inaccuracy in the teacher and staff payroll system, which is caused by the lack of a standardized and transparent system. Errors in calculating salaries and determining reward criteria often result in injustice, where teachers with higher experience and qualifications receive disproportionate salaries, thus reducing motivation and affecting the quality of teaching. The system method uses the waterfall model and system modeling uses use case diagrams, class diagrams, and activity diagrams. And the results of this study are in the form of an e-barokah application design.